2020
DOI: 10.33105/itrev.v5i4.175
|View full text |Cite
|
Sign up to set email alerts
|

Inefisiensi Belanja Pemerintah Daerah di Indonesia: Pendekatan DEA dan Regresi Logit

Abstract: Tujuan penelitian ini adalah untuk mengukur Tujuan penelitian ini adalah untuk mengukur (1) efisiensi relatif penggunaan belanja seluruh pemerintah daerah setiap provinsi di Sumatera, dan (2) efisiensi relatif penggunaan belanja pemerintah kabupaten/kota di provinsi di Sumatera tahun 2016.   Input yang digunakan ada dua, yaitu belanja langsung per kapita dan belanja tidak langsung per kapita. Output yang dipakai adalah IPM. Metode pengukuran efisiensi yang digunakan adalah Data Envelopment Analysis (DEA), deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
4
6
0
7
Order By: Relevance
“…With an input minimization orientation, in general, districts in underdeveloped regions can reduce their actual expenditures by 39.9 percent in 2017, 42.9 percent in 2018, and 42.8 percent in 2019 with reference to other districts that have been efficient. This research is in line with research conducted by Rambe (2020) which shows that government expenditure in education, health, social protection, and economy is also still inefficient, meaning that government expenditure in the four fields is considered not to be allocated optimally.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…With an input minimization orientation, in general, districts in underdeveloped regions can reduce their actual expenditures by 39.9 percent in 2017, 42.9 percent in 2018, and 42.8 percent in 2019 with reference to other districts that have been efficient. This research is in line with research conducted by Rambe (2020) which shows that government expenditure in education, health, social protection, and economy is also still inefficient, meaning that government expenditure in the four fields is considered not to be allocated optimally.…”
Section: Resultssupporting
confidence: 87%
“…The probability of fiscal transfer per capita is below 5 percent, so H0 is rejected. The results of this analysis are supported by research conducted by Rambe (2020), Tuladhar (2014), andYusfany (2015). Weingast (2009) explains that transfers or grants from the central government can reduce the accountability of local governments in their fiscal decisions.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The next stage of this research will analyse the factors that affect the level of efficiency of local governments. Several previous studies have revealed these factors, such as GDP per capita (Antonelli & De Bonis, 2018;Brini & Jemmali, 2016), population density (Doumpos & Cohen, 2014), and fiscal capacity (Rambe, 2020b).…”
Section: Introductionmentioning
confidence: 93%
“…Efisiensi didefinisikan sebagai rasio antara masukan dan keluaran (rasio output per unit input). Suatu organisasi dianggap efisien jika dapat memperoleh keluaran tertentu berdasarkan masukan seminimal mungkin atau dengan masukan tertentu dapat menghasilkan keluaran semaksimal mungkin (Rambe, 2020). Dalam konteks belanja prioritas pemerintah berupa program padat karya, ukuran efisiensi dilihat dari besaran realisasi anggaran dalam pelaksanaan program padat karya untuk menyerap tenaga kerja secara maksimal dengan tujuan mengurangi angka pengangguran.…”
Section: Pemerintahunclassified